Iwo Friends Went on a Journey: Yizhar Smilansky and Yechi’am Weitz - Ma'apil, Avi (MiKAN, 2008)
S. Yizhar writing is known for the appropriation of social-historical materials. This is particularly true in Days of Ziklag (1958), his grand epos on the War of Independence, and other war stories such as "The Story of Hirbet Hiz’ah" or "The Prisoner". However, the central axis of S. Yizhar’s fiction is in fact explicitly autobiographical. One example of this is the dominant and continued presence of Yechi’am Weitz in S. Yizhar’s stories. Yechi’am, Yizhar’s cousin and close friend, was killed in the summer of 1946. Already several months after his death Yizhar wrote about him an elegiac and charged story, "Rainy Road", which has not yet been compiled into a book. At the same time, Yizhar wasIXworking on editing The Letters of Yechi’am Weitz (1948). Even before Yechi’am’s death, Yizhar wrote a wild farce about him entitled "Uncle Yechi’el is Hunting thieves" (1950). S. Yizhar returned to the figure of Yechi’am in his war story "Before leaving" (1959) and in his children’s story "Tarazinas" which was included in the compilation Bare Footed in the same year. s. Yizhar "planted"Yechi’am’s thinly veiled character, under the name "Amichai", within the group of fighters in Days of Ziklag (1958). Yechi’am is presented also in several oblique but meaningful references in Stories of the Plain (1963). 993 ו saw the publication of Yizhar’s book Zalhavim in which Yizhar returned to his good friend Yechi’am in his youth and reconfigured it in loving detail. The two friends, Yechi’am and Yizhar, went on a long journey. Almost fifty years separate Zalhavim and "Rainy Road"; through careful observation of the way in which Yizhar attempted to grasp the inner life of Yechi’am Weitz and the personal and social dilemmas which shaped him, it is possible to learn about the world of S. Yizhar himself.